2021
DOI: 10.3390/ma14216310
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Friction Performance of Lubricants with Nano Additives

Abstract: It has been established in literature that the addition of nanoparticles to lubricants at an optimum concentration results in a lower coefficient of friction compared to lubricants with no nanoparticle additives. This review paper shows a comparison of different lubricants based on the COF (coefficient of friction) with nanoadditives. The effect of the addition of nanoparticles on the friction coefficient was analyzed for both synthetic and biolubricants separately. The limitations associated with the use of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 89 publications
(119 reference statements)
0
25
0
Order By: Relevance
“…It can be observed that up to 2 vol % NA-containing inks (A50N1D2 and A50N2D2) show lower η than the NA-free (A50N0D2) and higher NA-retaining (3 and 4 vol %) inks (Figure c). The inclusion of NPs in a suspension at a certain concentration exhibits a lesser coefficient of friction and improved tribological properties than the NP-free suspension. , Spherical or quasi-spherical geometry NPs form a protective layer between the interacting MA surfaces where NAs produce a nano ball-bearing effect that modifies the sliding friction into rolling friction and minimizes wear-loss (Figure d). , The NPs act as a nanolubricant that helps reduce the η of ink. However, a high volume of NAs creates a jam between the contact surfaces of MAs and impedes the motion of particles attributed to a high η in ink.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that up to 2 vol % NA-containing inks (A50N1D2 and A50N2D2) show lower η than the NA-free (A50N0D2) and higher NA-retaining (3 and 4 vol %) inks (Figure c). The inclusion of NPs in a suspension at a certain concentration exhibits a lesser coefficient of friction and improved tribological properties than the NP-free suspension. , Spherical or quasi-spherical geometry NPs form a protective layer between the interacting MA surfaces where NAs produce a nano ball-bearing effect that modifies the sliding friction into rolling friction and minimizes wear-loss (Figure d). , The NPs act as a nanolubricant that helps reduce the η of ink. However, a high volume of NAs creates a jam between the contact surfaces of MAs and impedes the motion of particles attributed to a high η in ink.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The inclusion of NPs in a suspension at a certain concentration exhibits a lesser coefficient of friction and improved tribological properties than the NP-free suspension. 32,33 Spherical or quasi-spherical geometry NPs form a protective layer between the interacting MA surfaces where NAs produce a nano ball-bearing effect that modifies the sliding friction into rolling friction and minimizes wear-loss (Figure 4d). 34,35 The NPs act as a nanolubricant that helps reduce the η of ink.…”
Section: Rheological Behaviors Of Inksmentioning
confidence: 99%
“…With the development of nanoscience and nanotechnology, nanoscale-based lubricant additives have become a key research area in tribology. Frequently used nanoscale lubricant additives are metals, metal oxides, metal sulfides, metal borates, polymers, and carbon-based nanomaterials [18][19][20]. However, nanoscale carbon materials have become increasingly popular in the lubricant additive community due to their ecologically approachable nature, exceptional self-lubricating behavior, good chemical and high thermal stability and outstanding mechanical properties with respect to bulk carbon materials [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Lubrication oils, plastic greases and solid lubricants can be distinguished. Currently, there is a tendency to replace lubricating oils and plastic greases with solid lubricants [ 6 , 7 , 8 , 9 , 10 ]. Oils and plastic greases can pose a serious problem in some applications, for example, at high temperatures, when they may evaporate.…”
Section: Introductionmentioning
confidence: 99%